2014
DOI: 10.1123/jpah.2013-0175
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy, Action Control, and Social Support Explain Physical Activity Changes Among Costa Rican Older Adults

Abstract: The effect of self-efficacy on physical activity was partly explained by action control, providing evidence of action control as a proximal mediator of physical activity. Moreover, the moderator role of social support was confirmed: high social support appeared to compensate for low levels of self-efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 21 publications
0
26
1
Order By: Relevance
“…Notably, the path between social support and planning was also non-significant, suggesting that the receipt of social support from family members may not inform parents' decisions to make plans to be active. In contrast to current findings, previous research has shown a significant path between social support and planning (Reyes Fernandez, Montenegro, Knoll, & Schwarzer, 2014). Despite previous research suggesting that a supportive social network may be particularly important to buffer an individual's volitional strength to develop and enact plans (Schwarzer, 2008), the current sample of parents of very young children may not prioritize the receipt of social support from others in relation to their PA behaviour.…”
Section: Discussioncontrasting
confidence: 99%
“…Notably, the path between social support and planning was also non-significant, suggesting that the receipt of social support from family members may not inform parents' decisions to make plans to be active. In contrast to current findings, previous research has shown a significant path between social support and planning (Reyes Fernandez, Montenegro, Knoll, & Schwarzer, 2014). Despite previous research suggesting that a supportive social network may be particularly important to buffer an individual's volitional strength to develop and enact plans (Schwarzer, 2008), the current sample of parents of very young children may not prioritize the receipt of social support from others in relation to their PA behaviour.…”
Section: Discussioncontrasting
confidence: 99%
“…When social support is the focus of a dietary intervention, it should, however, be kept in mind that support can also be perceived as controlling or overprotecting and needs to be provided in a sensitive way (e.g., Silverman, Hecht, & McMillin, 2002). Because previous research has found that the interaction between self-efficacy and social support is associated with other health behaviors and self-regulatory strategies (Reyes Fernández et al, 2014;, future research should be conducted in order to further examine their synergistic effects on post-motivational self-regulatory processes.…”
Section: Discussionmentioning
confidence: 98%
“…Bandura's socialcognitive theory (1997) comprises social support as a sociostructural facilitator, which potentially moderates the effects of self-efficacy . Given recent evidence on the role of received social support to prompt self-regulatory strategies within the motivation process for physical activity (Reyes Fernández et al, 2014), this study aimed to examine the moderating role of received dietary social support in the dietary motivation process and its subsequent effect on fruit and vegetable intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived self-eicacy has been applied to many diferent domains such as self-regulated behaviour, and patients with arthritis [9], physical activity [10], multiple sclerosis [11] or addictive behaviours [12] but it has received scant atention in relation to CD. Although Bandura [6] proposes a speciic self-eicacy expectation narrowly linked to each situation, some authors [13,14] work with the hypothesis of a more general self-eicacy belief that accounts for behaviour in diferent domains in life.…”
Section: Social Cognitive Theory Self-eicacy and Gluten-free Dietmentioning
confidence: 99%